Development of Learning Media for Snakes and Ladders Integrated with Islamic Values in Class VII Flat Shape Materials - Hasri Muliati; Halimah, Andi; Abrar, Andi Ika Prasasti (Alauddin Journal of Mathematics Education, 2022)
This study aims to determine the characteristics of learning media that were developed to improve student learning outcomes in flat shape material. The trial phase was carried out 2 times, namely first, a limited trial that was tested on 10 randomly selected class VII.B students and a field trial was tested in the actual class, namely class VII.A with a total of 20 students. The research used is Research and Development (R&D) using the ADDIE development model with five stages, namely: (1) Analysis stage, (2) Design stage, (3) Development stage, (4) ) Implementation stage (Implementation) and (5) Evaluation stage (Evaluation). The product developed is in the form of learning media for snakes and ladders integrated with Islamic values ​​which contain flat shape material. The test subjects in this study were class VII students of SMP Negeri 2 Arungkeke. Based on the results of the study, it was found that, (1) Validity, the average validation results for the media and all research instruments was 85.6%, which means that the media and instruments are in the very valid category, (2) Practical, the average of all aspects of the practicality of the media is 92% is in the very good category, (3) the average of all aspects of effectiveness is 89.9% is in the very good category, so that the development of snakes and ladders learning media has met the criteria of validity, practicality and effectiveness.